Dual Visible Light‐Triggered Photoswitch of a Diarylethene Supramolecular Assembly with Cucurbit[8]uril. Issue 58 (21st September 2017) - Liu, Guoxing; Zhang, Ying‐Ming; Wang, Conghui; Liu, Yu
Abstract: Research on photochromic molecules switched by visible light is of particular interest for their application in bioimaging and stimuli‐responsive materials. Here, a photoswitchable supramolecular assembly comprised of monocharged bispyridinium‐modified diarylethenes (DAEs) and cucurbit[8]uril (CB[8]) has been constructed, which exhibits reversible photochromic behaviour with visible light in both directions. The transformation of CB[8] not only prompts the DAEs to form charge‐transfer complexes, but also restricts its intramolecular rotation to enhance fluorescence emission. In this CB[8]‐containing supramolecular system, the π‐conjugation is extended and its absorption is bathochromically shifted for visible light‐driven cyclization of DAEs. Meanwhile, the fluorescence of the supramolecular assembly can also be reversibly modulated by visible light. These findings may furnish a new strategy for the development of visible light‐driven fluorescent biomaterials and molecular machines. Abstract : Switching on the lights : A photoswitchable supramolecular assembly comprised of monocharged bispyridinium‐modified diarylethene and cucurbit[8]uril has been constructed, exhibiting reversible photochromic behaviour and tunable fluorescence emission with visible light in both directions.